2021
DOI: 10.1002/cbdv.202100651
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antifungal Activity, DFT Study and Molecular Dynamics Simulation of Novel 4‐(1,2,4‐Oxadiazol‐3‐yl)‐N‐(4‐phenoxyphenyl)benzamide Derivatives

Abstract: In order to find novel potential antifungal agrochemicals, a series of new 4-(1,2,4-oxadiazol-3-yl)-N-(4phenoxyphenyl)benzamide derivatives 3a-j were designed, synthesized and characterized by their 1 H-, 13 C-NMR and HRMS spectra. The preliminary antifungal assay in vitro revealed that compounds 3a-j exhibited moderate to good antifungal activity against five plant pathogenic fungi. Especially, compound 3e presented significant antifungal activity against Alternaria solani, Botrytis cinerea and Sclerotinia sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Smaller gaps, indicating easier electron transfer, are associated with higher polarizability and enhanced reactivity, while larger gaps signify greater stability and lower reactivity [27]. By studying the properties of the HOMO and LUMO, we can gain valuable information about a molecule's susceptibility to reactions, its capacity for excited-state behavior, and its propensity to interact with other molecules, all of which contribute to understanding its potential biological activity [28]. The calculated energy values for the FMOs (EHOMO, ELUMO) and their energy gaps, as well as the global reactivity descriptors in the absence of a solvent, are mentioned in Table 1.…”
Section: Global Reactivity Indicesmentioning
confidence: 99%
“…Smaller gaps, indicating easier electron transfer, are associated with higher polarizability and enhanced reactivity, while larger gaps signify greater stability and lower reactivity [27]. By studying the properties of the HOMO and LUMO, we can gain valuable information about a molecule's susceptibility to reactions, its capacity for excited-state behavior, and its propensity to interact with other molecules, all of which contribute to understanding its potential biological activity [28]. The calculated energy values for the FMOs (EHOMO, ELUMO) and their energy gaps, as well as the global reactivity descriptors in the absence of a solvent, are mentioned in Table 1.…”
Section: Global Reactivity Indicesmentioning
confidence: 99%
“…14. 70 Based on the fungicide flufenoxadiazam, the intriguing diaryl ether substructure was introduced at the amine's side site. The preliminary in vitro antifungal assay indicated that most of the synthesized compounds exhibited moderate to good fungicidal activity against five plant pathogenic fungi at 20 mg L −1 ( Botrytis cinerea , Rhizoctonia solani , Sclerotinia sclerotiorum , Alternaria solani , and Gibberella zeae ).…”
Section: 24-oxadiazole Derivatives With Pesticidal Activitymentioning
confidence: 99%
“…Another antifungal application of TFMO containing compounds was reported by Yang et al [22]. The design of active compounds was guided by previous TFMO HDACi and diphenyl ether moieties, frequently used in pesticides.…”
Section: Zbg Scaffoldsmentioning
confidence: 99%